The Impact of Madrasah Principal Accountability on the Quality of Islamic Religious Education Learning - Delfita Nurhidayati; Muttaqin Muttaqin; Lilis Setiawati; Muhammad Agus Zainan Junaidi; Baili Baili; Mabruri Mabruri (The Future of Education Journal, 2025)
This study aims to analyze the forms and implementation of madrasah principal accountability and its impact on the quality of Islamic Religious Education (IRE) learning processes and outcomes at SMP Darul Hasanah Al Inayah 2. The study employed a qualitative approach with a descriptive field research design. The research participants consisted of the madrasah principal and several teachers, particularly Islamic Religious Education teachers. Data were collected through observations, interviews, and documentation. The collected data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the accountability of the madrasah principal is manifested through the planning of instructional programs, the implementation of academic supervision, the management of educational resources, and the transparent reporting of educational activities to relevant stakeholders. The implementation of such accountability has a positive impact on improving the quality of Islamic Religious Education learning, both in terms of more structured and effective learning processes and enhanced teacher competence in conducting instructional activities. Therefore, madrasah principal accountability plays a crucial role in improving the quality of both the learning process and learning outcomes in Islamic Religious Education.